State-aided Price Coordination in the Dutch Mortgage Market - Mark A. Dijkstra; Maarten-Pieter Schinkel (Tinbergen Institute, 2019)
We show how price leadership bans, imposed as part of the European Commission's State aid control on all main mortgage providers except the largest bank, shifted the Dutch mortgage market from a competitive to a collusive price leadership equilibrium. In May 2009, mortgage rates in the Netherlands suddenly rose against the decreasing funding cost trend to almost a full percentage point above the Eurozone average. We derive equilibrium best-response functions, identify the price-leader, and estimate response adjustments in daily household mortgage rates between 2004 and 2012. Around the Spring of 2009, when the bans were collectively negotiated, we find structural decreases in the leader's cost pass-through, much closer following of its price, and strongly reduced transmissions of common cost changes into price-followers' mortgage rates. Indicative predicted overcharges are 125 basis points or 26%, on average.
Keywords: L11; G21; L85; 330; banking; competition; price leadership; collusion; State aid